Metabolomic characteristics of aerobic and resistance exercise modes - Junjie Kuang; Jie Ju; Xin Xu (PLoS ONE, 2025)
Aerobic and resistance exercises are the two most common modes of physical activity. They may cause some functional changes such as elevation of VO2max and muscle mass. However, descriptions of changes in complex molecular network induced by exercise are often insufficiently comprehensive, limiting the exploration of some new indicators. We utilized a metabolomics analysis method based on Liquid chromatography-mass spectrometry (LC-MS) to investigate the metabolic characteristics of 10 healthy male college students at two time points before and after a single session of aerobic and resistance exercise. The analysis was conducted at both the metabolite and metabolic pathway levels. Notably, the concentrations of several amino acids including aspartic acid, glutamic acid, histidine and tryptophan exhibited significant changes following both modes of exercise. These findings offer a more comprehensive understanding of the molecular effects of acute exercise on the human body, contributing to evaluating post-exercise physiological states and screening for relevant metabolite indicators. Future research could employ multi-omics approaches to validate these results and explore the long-term impact of exercise on human metabolic profiles, linking specific metabolic pathways to functional outcomes.